2016
DOI: 10.1182/asheducation-2016.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia: sequencing of TKI therapies

Abstract: Multiple tyrosine kinase inhibitors (TKIs) are available for managing patients with chronic myeloid leukemia. Although most patients have a favorable outcome with their initial therapy, whether imatinib or a second-generation TKI was used, some will require subsequent use of one or more different TKIs. Such sequencing might be indicated in a reactive way (ie, for patients who have experienced resistance or intolerance to their initial therapy) or in a proactive way (ie, for patients with a somewhat favorable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
1
15
0
3
Order By: Relevance
“…Recent data have revealed that an increasing number of patients may gradually achieve a deep molecular response (DMR) if they continue to use second‐generation TKI for several years . However, increasing concern surrounds the long‐term adverse effects and financial burden associated with TKI …”
Section: Introductionmentioning
confidence: 99%
“…Recent data have revealed that an increasing number of patients may gradually achieve a deep molecular response (DMR) if they continue to use second‐generation TKI for several years . However, increasing concern surrounds the long‐term adverse effects and financial burden associated with TKI …”
Section: Introductionmentioning
confidence: 99%
“…The sequential indication of the three available TKIs, in our universe, do not differ from the ones suggested in different spheres [18,19]. The causes for changes to second or third line were the lack of response and in only one case, toxicity.…”
Section: Discussionmentioning
confidence: 51%
“…In prospective studies, however, greater efficacy has been shown with nilotinib or dasatinib [8,19]. The practice of using TKIs sequentially, in relation to the response to the first or second line, has become more widespread, and is frequently recommended [18,19]. In our case, the lack of response was the most frequent condition.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Dasatinib is a highly potent, second‐generation BCR‐ABL1 tyrosine kinase inhibitor (TKI) that also inhibits other kinases in addition to ABL. Dasatinib and other second‐generation TKIs have all demonstrated efficacy after imatinib failure in all stages of chronic myeloid leukemia (CML) . A long‐term follow‐up of dasatinib after imatinib failure showed a major cytogenetic response (MCyR) in 59% of patients, with 7‐year and overall survival (OS) rates of 65% …”
Section: Introductionmentioning
confidence: 99%